DefectAnalysis on Smoothmill Facility Using Priority-Cost Failure Mode, Effect, And Criticality Analysis (PC-FMECA) MethodsatPT. Ebako Nusantara - Arfan Bakhtiar, Bambang Purwanggono Ranintia Adhi Citra Pramesti (USIM, TAMKANG, khon kaen, UMY, 2016)
FMEA (Failure Mode and Effects Analysis) is a method to identify potential failure modes of a process or product, which has been used since 1950 inside an aviation control system. To implement more efficient improvement of FMEA, criticality analysis was then added into every failure mode, termed Failure Mode, Effects, and Criticality Analysis (FMECA). However, those methods are yet to integrate cost variable, which are essential in the rapid growth of manufacturing industries. Priority-Cost FMECA (PC-FMECA) emerged to reach such objective.